Potencial antibacteriano e modulador de resistência a drogas de extratos e constituintes de algas marinhas em staphylococcus aureus - Silva, Suellen Maria Pinto de Menezes (2013)
The mechanism of antimicrobial resistance is a genetic phenomenon related to the existence of genes contained in the microorganism that encode proteins responsible for biochemical mechanisms that prevent the action of drugs. The increasing incidence of resistant bacteria has undermined the therapeutic value of available antibacterials, creating the necessity, increasingly, the search for alternatives that can reverse or decrease the resistance, as the search for inhibitors of resistance mechanisms. Efflux pumps, which are transmembrane proteins involved in transport of substrates toxic, has been responsible for many cases of bacterial resistance to antibiotics and being associated with multidrug resistance. "Modifiers of drug resistance", "Modifiers of antibiotic activity" and "Adjuvant antibiotic" are terms used for drugs that modulate bacterial resistance to antibiotics, which may act by inhibiting the efflux system. In the present study, we evaluated extracts of Dictyota pulchella and Sargassum polyceratium and their isolated compounds, diterpene and pheophytin as possible efflux pump inhibitors; extracts: Gracilaria cervicornis, Sargassum polyceratiu,; Mexican Caulerpa, Caulerpa kempfii, hondrophycus papillosus, Dictyota pulchella and Sargassum polyceratium with antibacterial activity mediated by UV- A Light. We used bacterial strains expressing the gene norA, msrA or tetK encoding efflux proteins for some compounds, such as norfloxacin (Nora), erythromycin (MSRA) and tetracycline (TetK), respectively. Through the microdilution technique using nutrient broth, were determined values of minimum inhibitory concentrations (MIC) of antibiotics, algae extracts and constituents, and to evaluate the activity modulator, MICs of the antibiotics were determined in the absence and presence of concentrations subinibitory natural products. None of the extracts or constituents tested showed significant antibacterial activity (MIC ≥ 256μg/mL), however, two of the extracts, Dictyota and Sargassum and their constituents phaeophytin and diterpene showed modulatory activity in the strains tested. They reduced values between 2 and 16 times. The extracts of Dictyota and Sargassum also showed antibacterial activity median for light. The results presented here describe for the first time tested these extracts and constituents acting as a putative inhibitor of the efflux system in bacteria, and also phototoxic activity. Therefore, natural products seaweed may serve as source products which modulate the bacterial resistance, ie as antibiotics adjuvants potential.